Pendidikan Karakter Berbasis Hukum Waris Islam: Strategi Kontekstual dalam Menjawab Tantangan Moral Modern - Agus Sulistyo; Enik Nur Faizah; Rahmat Ryadhush Shalihin (At Turots: Jurnal Pendidikan Islam, 2024)
This study aims to explore the potential integration of Islamic inheritance law, particularly the concept of murder as a disqualifier for inheritance rights (māni’ al-mīrāṡ), as a medium for character education within the Islamic Religious Education (PAI) curriculum. Family conflicts over inheritance disputes, often culminating in acts of murder, provide a critical context for connecting moral values such as justice, responsibility, and respect for life to ethics-based learning. This approach innovatively employs the normative concepts of Islamic law as a character development tool, addressing the modern era's moral challenges. The study adopts a qualitative-descriptive methodology, incorporating analyses of Islamic law literature and character education frameworks. Primary sources include the Qur’an, Hadith, and classical jurisprudential texts such as Al-Mughni by Ibn Qudamah and Al-Ahkam As-Sulthaniyyah by Al-Mawardi. Secondary sources encompass literature on character education and learning strategies. Content analysis is employed to identify the moral values inherent in Islamic inheritance law and their relevance to character education using case-based studies. The findings indicate that Islamic inheritance law can effectively function as a tool for character education, fostering values such as self-control, respect for life, and ethical conflict resolution. Case-based learning and problem-based learning (PBL) approaches prove effective in integrating these themes into the moral and religious character formation of students. This study offers a novel, contextual, and practical approach distinct from conventional teaching methods, addressing the increasingly complex moral challenges posed by materialism and individualism in society.